Switchover Mode of Reproduction and the Problem of Coordination - Mayevsky, Vladimir Ivanovich (Economy of Regions, 2015)
The proposed version of macroeconomic theory of capital reproduction is related to thethesis that the dynamics of the economy are caused by the change in generations of capital and there is a problem of coordination between these generations. This paper discusses the so-called “switchover mode of reproduction”. As shown by the mathematical model, a coordinated growth is possible when the social and economic interests are agreed between the labor and the capital, as well as under a monetary policy that stimulates such growth. An uncoordinated growth poses a threat of economic crisis.